2014
DOI: 10.1038/srep03930
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photovoltaic performance of Cu-based metal-organic frameworks sensitized solar cell by addition of carbon nanotubes

Abstract: In the present work, TiO2 nanoparticle and multi-walled carbon nanotubes composite powder is prepared hydrothermally. After doctor blading the paste from composite powder, the resulted composite film is sensitized with Cu-based metal-organic frameworks using a layer-by-layer deposition technique and the film is characterized using FE-SEM, EDX, XRD, UV/Visible spectrophotometry and photoluminescence spectroscopy. The influence of the carbon nanotubes in photovoltaic performance is studied by constructing a Grät… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Covalent bonds can exist in MOF hybrid materials made using this method but are not as common, so we include relevant examples in the "Covalent Modification" section (hybrids made from ALD and COF-MOF hybrids). Using this technique, metal clusters, metal oxides, graphene oxide, and polymers have been hybridized with MOFs, giving rise to new materials that are useful in gas separation, catalysis, photovoltaics, and proton conducting [52,53,56,[66][67][68][69]. The notation A|B|C is used to represent materials A, B, and C that are hybridized via layer-layer deposition.…”
Section: Layer-by-layer Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalent bonds can exist in MOF hybrid materials made using this method but are not as common, so we include relevant examples in the "Covalent Modification" section (hybrids made from ALD and COF-MOF hybrids). Using this technique, metal clusters, metal oxides, graphene oxide, and polymers have been hybridized with MOFs, giving rise to new materials that are useful in gas separation, catalysis, photovoltaics, and proton conducting [52,53,56,[66][67][68][69]. The notation A|B|C is used to represent materials A, B, and C that are hybridized via layer-layer deposition.…”
Section: Layer-by-layer Depositionmentioning
confidence: 99%
“…More recently, MOF hybrid membranes were found useful in solar energy harvesting and conversion [52,66,69]. Lee et al prepared a TiO 2 |nanotube|MOF hybrid membrane that showed enhanced photovoltaic performance [66]. A composite film containing TiO 2 nanoparticles and multi-walled carbon nanotubes was first synthesized hydrothermally.…”
Section: Layer-by-layer Depositionmentioning
confidence: 99%
“…Nevertheless, using MOFs for fabricating full solar cell devices is rarely investigated. More recently, MOF thin films have been demonstrated as sensitizers for solar radiation harvesting in a TiO 2 -based liquid junction solar cells [12] . The device had an I sc of 1.25 mA cm -2 , V oc of 0.49 V, fill factor of 0.43, and power conversion efficiency of 0.26%.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, carbon nanotubes (CNTs), tubular analogue to graphene sheets, may be an alternative carbon to facilitate MOFs adsorbing target compounds and to enhance MOFs photocatalytic activity under visible light (Cong et al, 2011;You et al, 2013). However, rare studies reported the addition of CNTs into MOFs and evaluated its effect on adsorption in water and photocatalytic activity in the literature (Anbia and Sheykhi, 2013;Lee et al, 2014). Therefore, in this study, we investigate the effects of amine, CNTs and reduced graphene oxide (RGO) on MOF's adsorptive and photocatalytic performances to remove dyes from water.…”
Section: Introductionmentioning
confidence: 99%